2020
DOI: 10.3390/app10155284
|View full text |Cite
|
Sign up to set email alerts
|

Fast Self-Adaptive Digital Camouflage Design Method Based on Deep Learning

Abstract: Traditional digital camouflage is mainly designed for a single background and state. Its camouflage performance is appealing in the specified time and place, but with the change of place, season, and time, its camouflage performance is greatly weakened. Therefore, camouflage technology, which can change with the environment in real-time, is the inevitable development direction of the military camouflage field in the future. In this paper, a fast-self-adaptive digital camouflage design method based on deep lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Troop camouflage in military operations is indispensable to trick and move as close as possible to the opponent, while from the opponent's side constantly trying to extract field conditions from possible enemy camouflage. Separately, the development of artificial intelligence has provided many benefits for recognition and detection purposes [1]. However, the problem of camouflage detection is considered to be difficult to overcome because distinguishing between objects and the same background requires a different strategy [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Troop camouflage in military operations is indispensable to trick and move as close as possible to the opponent, while from the opponent's side constantly trying to extract field conditions from possible enemy camouflage. Separately, the development of artificial intelligence has provided many benefits for recognition and detection purposes [1]. However, the problem of camouflage detection is considered to be difficult to overcome because distinguishing between objects and the same background requires a different strategy [2].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the testing of this work uses artificial targets. It is similar with using deep learning; you only look once (YOLOv3) with an average accuracy of 91.55% [1]. Furthermore, it turns out that Xiao et al [1] used a camouflage dataset that was not considered as a vague, for example, a fighter plane with a sky background or a frigate with an ocean background.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They trained a YOLOv3 model to identify desired targets in the scenes and then, a pretrained deepfillv1 model was utilized to generate primary camouflage texture. Finally, they standardized the primary camouflage texture using the K‐means algorithm 12 …”
Section: Introductionmentioning
confidence: 99%
“…Finally, they standardized the primary camouflage texture using the K-means algorithm. 12 As the above literature review indicated, all methods generate a CP from scratch based on background images. However, generating a pattern from scratch using a background image tends to lead to high dimensional space of parameters that is time-consuming.…”
Section: Introductionmentioning
confidence: 99%